Off-Label Use of Antineoplastic Drugs to Treat Malignancies: Evidence From China Based on a Nationwide Medical Insurance Data Analysis - Wei, Guoxu; Wu, Min; Zhu, He; Han, Sheng; Chen, Jing; Zhai, Chenchen; Shi, Luwen (Frontiers in Pharmacology, 2021)
Abstract Purpose: Cancer is a leading cause of morbidity and mortality worldwide. Off-label (OL) use of antineoplastic drugs to treat malignancies is prevalent. In this study, we quantified and characterized OL use of antineoplastic drugs to treat malignancies in China. Methods: This was a retrospective study using nationwide data collected from 2008 to 2010. Use of antineoplastic drugs was considered OL if they were used for indications not reﬂected in the package insert published by the National Medical Products Administration at the time of prescription. Descriptive analysis and Spearman rank correlation were used to evaluate the frequency and pattern of OL drug use. Results: In total, 51,382 patients with malignancies, 24 categories of antineoplastic drugs, and 77 types of malignancies treated with OL drugs were included in this study. Twenty commonly used antineoplastic drugs (ICD encoded as L01) were used OL in 10-61% of cases, and four commonly used endocrine therapy antineoplastic drugs (ICD encoded as L02) were used OL in 10-19% of cases. There was a significant negative correlation between the disease constituent ratio and the average OL use rate of antineoplastic drugs for various malignancies. In contrast, there was a significant positive correlation between the average OL use rate of antineoplastic drugs and the number of malignancies treated with OL drugs. Conclusion: This study provided information regarding OL use of antineoplastic drugs for treatment of malignancies, and showed that OL use was prevalent. In addition, uncommon malignancies were more likely to be treated with OL antineoplastic drugs. Furthermore, more commonly used antineoplastic drugs were more likely to be used OL.